Age-dependent vulnerability of cyclosporine-associated encephalopathy in children. (July 2015) - Chen, Li-Wen; Chen, Jiann-Shiuh; Tu, Yi-Fang; Wang, Shan-Tair; Wang, Lan-Wan; Tsai, Yi-Shan; Huang, Chao-Ching
Abstract Introduction Cyclosporine (CsA) is an immunosuppressant known for its neurotoxicity, which presents with acute encephalopathy and seizures in the most severe form. However, whether there is age-related neurological susceptibility in pediatric population is poorly defined. The study aims to examine the vulnerability of CsA neurotoxicity among different age groups of pediatric patients in terms of occurrence rate, acute presentations, long-term outcomes, and neuroimaging findings. Methods Pediatric patients (age <18 years) who received CsA in a tertiary referral center between July 1, 1988 and August 31, 2011 were retrospectively reviewed for CsA-related encephalopathy. The clinical presentations, demographic data, and laboratory examinations were analyzed through t-test for numerical and Fisher's exact test for categorical variables. Exact logistic regression was used to examine the effect of each variables. Results Twelve (8%) of the enrolled 146 patients developed CsA-induced encephalopathy. Compared to the non-neurotoxicity group, the neurotoxicity group was significantly younger upon starting CsA (p = 0.008) and had higher percentages of hypertension after CsA treatment (p = 0.01). Regression analysis showed that age <6 years (OR 7.6, 95% CI 1.6–51.5; p = 0.007) and hypertension after CsA (OR 6.3, 95% CI 1.4–35.4; p = 0.016) were significantly associated with CsA encephalopathy. Younger children were prone to have more severe seizures in the acute stage and more epilepsy and neuropsychiatric disorders in the future. Follow-up neuroimaging showed parietal cerebral atrophy in all examined children <6 years of age. Conclusions Age-dependent susceptibility of CsA neurotoxicity occurs in children, with severe acute presentations and long-term sequelae in children below 6 years old.